Bilateral globus pallidus interna deep brain stimulation in the treatment of mixed cerebral palsy in ataxia with dyskinesia: a case report - Chang, Lei; Luo, Bei; Dong, Wenwen; Qiu, Chang; Lu, Yue; Sun, Jian; Yan, Jiuqi; Zhang, Wenbin; Yan, Jun (Frontiers in Neurology, 2023)
Background: Cerebral palsy (CP), a complex syndrome with multiple etiologies, is characterized by a range of movement disorders within the hypokinetic and hyperkinetic spectrum (dystonia or choreoathetosis). CP is often accompanied by neurological and psychiatric signs, such as spasticity, ataxia, and cognitive disorders. Although current treatment options for CP include pharmacological interventions, rehabilitation programs, and spasticity relief surgery, their effectiveness remains limited. Deep brain stimulation (DBS) has demonstrated significant effectiveness in managing dyskinesia; however, its potential therapeutic effect on CP remains determined. Methods: We present a case of a 44-year-old Asian female who was born as a twin with neonatal ischemic-hypoxic encephalopathy due to prolonged labor and delivery. She was diagnosed with CP at the age of 1 year. The patient exhibited delayed development compared to her peers and presented with various symptoms, including slurred speech, broad-based gait, horseshoe inversion of the right lower extremity, involuntary shaking of the upper extremities bilaterally, and hypotonia and showed no improvement with levodopa therapy. Two years ago, she developed progressive head tremors, which worsened during periods of tension and improved during sleep. As medical treatments proved ineffective and there were no contraindications to surgery, we performed bilateral globus pallidus interna DBS (GPi-DBS) to alleviate her motor dysfunction. Results: Following a 6-month follow-up, the patient demonstrated significant improvements in motor symptoms, including head and limb tremors and dystonia. In addition, significant improvement was observed in her overall psychological well-being, as evidenced by reduced anxiety and depression levels. Conclusion: DBS is an effective treatment for dyskinesia symptoms associated with CP in adults. Moreover, its effectiveness may continue to increase over time.